Graphite-silicon composite material with silicon carbide layer and preparation method and application thereof

By covering the nanosilicon layer, carbon layer and outer cladding layer on the porous graphite matrix, and connecting nanoSi and graphite edge carbon nanotubes using silicon carbide chemical bonds, the existing graphite-silicon composite materials have high resistivity and low Coulomb efficiency, achieving excellent battery performance and extended battery life.

CN119695112APending Publication Date: 2025-03-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411875541.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing graphite-silicon composites have high resistivity and low Coulomb efficiency, which limits their application in lithium-ion batteries.

Method used

By sequentially covering the nanosilicon layer, the carbon layer and the outer cladding layer on the porous graphite matrix, the nanosilicon layer and the graphite edge carbon nanotubes are connected by chemical bonds of silicon carbide to form a graphite-silicon composite material with excellent conductivity.

Benefits of technology

It achieves better first-round Coulomb efficiency, specific capacity, fast charging performance and cycle performance, extends battery life, and has excellent overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695112A_ABST
    Figure CN119695112A_ABST
Patent Text Reader

Abstract

The invention provides a graphite-silicon composite material with a silicon carbide layer as well as a preparation method and application of the graphite-silicon composite material. The graphite-silicon composite material provided by the invention comprises a porous graphite matrix with a distributed carbon nanotube structure, a nano silicon layer, a carbon layer and an outer coating layer, wherein the nano silicon layer, the carbon layer and the outer coating layer are sequentially coated on the porous graphite matrix with the distributed carbon nanotube structure from inside to outside; and the nano silicon layer is connected with the carbon nano tube structure through silicon carbide chemical bonds. The graphite-silicon composite material disclosed by the invention has relatively good first-circle coulombic efficiency, quick charge performance and cycle performance when being applied to a battery, the specific capacity of the battery is improved, the service life of the battery is prolonged, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to lithium ion battery materials, and in particular to a graphite-silicon composite material with a silicon carbide layer and a preparation method and application thereof. Background Art

[0002] The growing demand for lithium-ion battery (LIB) energy density in electric vehicles and energy storage systems has accelerated the development of high-capacity anode materials for LIBs. Among these anodes, silicon is considered the most promising candidate due to its abundant natural reserves, high theoretical specific capacity, and suitable lithium insertion potential. However, the large volume expansion of silicon materials during the cycle will cause particle crushing, poor electrical contact, and continuous formation of the solid electrolyte interphase (SEI) layer, which seriously limits its development.

[0003] To overcome these serious obstacles, a lot of research has been devoted to the development of silicon nanoengineering based on porous structures, such as nanoparticles, nanowires and nanolayers. Although these silicon nanostructure engineering relieves the stress caused by volume change, it is hindered by its high resistivity and low Coulomb efficiency (CE) in industrial applications. For the practical application of nanoengineered silicon, incorporating silicon (Si) into graphite (Go) is considered to be a viable next-generation negative electrode material. CN112635733A patent prepares silicon-graphite composite materials by chemical vapor deposition (CVD) of gaseous silicon precursors, which not only improves the conductivity of Si, but also has a high initial Coulomb efficiency (ICE). Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the problems of high resistivity and low coulomb efficiency of graphite-silicon composite materials in the prior art. The present invention provides a graphite-silicon composite material with a silicon carbide layer and a preparation method and application thereof. The graphite-silicon composite material has good first-cycle coulomb efficiency, specific capacity, fast charging performance and cycle performance, prolongs battery life, and has excellent comprehensive performance.

[0005] The present invention provides a graphite-silicon composite material, which comprises a porous graphite matrix with a distributed carbon nanotube structure, a nano-silicon layer, a carbon layer and an outer coating layer; wherein the nano-silicon layer, the carbon layer and the outer coating layer are sequentially coated on the porous graphite matrix with the distributed carbon nanotube structure from the inside to the outside; the nano-silicon layer is connected to the carbon nanotube structure through a silicon carbide chemical bond.

[0006] In one embodiment, the carbon nanotube structure is distributed at the edges of the pores in the porous graphite matrix.

[0007] In a certain embodiment, the pore size of the porous graphite matrix with distributed carbon nanotube structure is 0.5-5 nm, preferably 1.5-2 nm or 2.5-3.5 nm.

[0008] In one embodiment, the pore volume of the porous graphite matrix with distributed carbon nanotube structure is 0.0015~0.5cm 3 / g, preferably 0.45cm 3 / g.

[0009] In one embodiment, the micropore ratio of the porous graphite matrix with distributed carbon nanotube structure is 0.5-0.9, preferably 0.85.

[0010] In a certain embodiment, the nano-silicon layer is deposited in the pores and on the surface of the porous graphite matrix with distributed carbon nanotube structure.

[0011] The carbon layer is a conventional carbon layer used in the field as a graphite-silicon composite material, preferably an ethylene carbon layer, an acetylene carbon layer or a methane carbon layer, such as an ethylene carbon layer.

[0012] In one embodiment, the outer coating layer is a polyacrylonitrile layer (PAN layer).

[0013] In a certain embodiment, the graphite-silicon composite material is composed of a porous graphite matrix with a distributed carbon nanotube structure, a nano-silicon layer, a carbon layer and an outer coating layer from the inside to the outside.

[0014] The present invention also provides a method for preparing a graphite-silicon composite material, which comprises the following steps:

[0015] S1: fusing a porous graphite matrix with a metal catalyst precursor to obtain a mixture of the porous graphite matrix and the metal catalyst precursor; in the presence of a carbon source, the porous graphite matrix and the metal catalyst precursor mixture are subjected to a vapor deposition method to obtain a porous graphite matrix with a distributed carbon nanotube structure;

[0016] S2: The silicon source is coated on a porous graphite substrate with a distributed carbon nanotube structure by a vapor deposition method to obtain a composite material coated with a nano-silicon layer;

[0017] The temperature of the vapor deposition method is ≤ 900°C;

[0018] S3: coating the carbon source on the composite material coated with the nano-silicon layer by a vapor deposition method to obtain a composite material coated with a carbon layer;

[0019] S4: coating the composite material coated with the carbon layer with a coating agent to obtain a graphite-silicon composite material.

[0020] In S1, the metal catalyst precursor is a conventional metal catalyst precursor with reducing properties in the art, preferably nickel nitrate or nickel nitrate hydrate, cobalt nitrate or cobalt nitrate hydrate, or iron nitrate or iron nitrate hydrate, such as Ni(NO3)2·6H2O.

[0021] In one embodiment, in S1, the mass ratio of the porous graphite substrate to the metal catalyst precursor is (5-15):1, preferably 10:1.

[0022] In one embodiment, in S1, the porous graphite substrate and the metal catalyst precursor mixture are subjected to hydrogen reduction treatment before vapor deposition. The temperature of the hydrogen reduction treatment is preferably 500-1000°C, preferably 700°C.

[0023] The time of the hydrogen reduction treatment is preferably 0.1-1 h, preferably 0.3 h or 0.5 h.

[0024] In S1, the carbon source is a carbon source conventionally used in the art for coating graphite-silicon composite materials, preferably ethylene gas, acetylene gas or methane gas, such as acetylene gas.

[0025] In one embodiment, in S1, the temperature in the vapor deposition method is 500~1000°C, preferably 700°C.

[0026] In one embodiment, in S1, the porous graphite matrix is ​​prepared by the following method: in the presence of CO2, pores are formed in graphite to prepare the porous graphite matrix.

[0027] The gas flow rate of the CO2 gas is preferably 15-25 mL / min, preferably 20 mL / min. The ventilation time of the CO2 gas is 1-5 hours, preferably 2 hours.

[0028] Before forming the pores, the graphite is preferably heated by a programmed temperature rising method.

[0029] In one embodiment, the temperature program is divided into two stages:

[0030] Stage 1: Heating rate is 1~5℃ / min, for example 1℃ / min; heating to 400℃ and keeping for 2h;

[0031] The second stage: the heating rate is 1-5°C / min, for example, 2°C / min, and the temperature is raised to 800°C.

[0032] In one embodiment, the heating is performed under an inert gas atmosphere, preferably nitrogen.

[0033] In one embodiment, in S2, the temperature of the vapor deposition method is 400~800°C, preferably 580~620°C, for example 600°C.

[0034] In one embodiment, in S2, the deposition pressure of the vapor deposition method is 10~50KPa, preferably 20 KPa.

[0035] In one embodiment, in S2, the deposition time of the vapor deposition method is 0.1 to 5 hours, preferably 1.16 hours.

[0036] In one embodiment, in S2, the silicon source is introduced into the fluidized bed as silane gas, preferably silane with a purity of 99.9999%.

[0037] In one embodiment, in S2, the silane gas is SiH4.

[0038] In one embodiment, before S3, silicon is deactivated by passing an inert gas (eg, nitrogen).

[0039] In one embodiment, in S3, the vapor deposition is carried out in an atmosphere with an oxygen content of ≤0.1 ppm.

[0040] In one embodiment, in S3, the vapor deposition temperature is 400-900°C, preferably 500-700°C, for example 600°C.

[0041] In S3, the carbon source is a carbon source conventionally used in the art for coating graphite-silicon composite materials, preferably ethylene gas, acetylene gas or methane gas, such as ethylene gas.

[0042] In one embodiment, in S3, the gas flow rate of the carbon source is 0.1-3 L / min, preferably 0.5 L / min.

[0043] In one embodiment, in S3, the reaction time is 0.5 to 5 hours, preferably 1 hour.

[0044] In one embodiment, in S4, the coating agent is polyacrylonitrile (PAN).

[0045] In one embodiment, in S4, the mass ratio of the composite material of the coated carbon layer to the coating agent is 1:(0.1-1), preferably 1:(0.2-0.4), for example 1:025.

[0046] In one embodiment, in S4, the coating further comprises the following steps:

[0047] The mixture of the composite material coated with the carbon layer and the solvent and the mixture of the coating agent and the solvent are mixed, dried and heated to obtain the graphite-silicon composite material.

[0048] In one embodiment, in S4, the coating solution is preferably stirred before coating, and the stirring time is 1 to 5 hours, for example, 2 hours.

[0049] In a certain embodiment, in S4, the coating is preferably dried after coating, and the drying temperature is 80~120°C, preferably 100°C; the drying time is 5~10h, preferably 8h.

[0050] In one embodiment, in S4, the heating temperature is 550-700°C, for example, 650°C.

[0051] In one embodiment, in S4, the heating time is 4 to 6 hours, for example 4.5 hours.

[0052] The present invention also provides a graphite-silicon composite material prepared by the above preparation method.

[0053] The present invention also provides a battery pole piece, which comprises the graphite-silicon composite material as described above, a binder and a conductive agent.

[0054] In the present invention, the conductive agent and the binder are conventional conductive agents and binders in the art.

[0055] In a certain embodiment, the conductive agent may be acetylene black (Super P).

[0056] In one embodiment, the binder may be polyacrylic acid (LA132).

[0057] In one embodiment, the solvent may be water, which serves as a dispersant to form the electrode slurry.

[0058] The present invention also provides a battery, which comprises the above-mentioned battery pole piece, a diaphragm and an electrolyte.

[0059] In one embodiment, the electrolyte is a LiPF6 solution, wherein the concentration of the solution is 1 mol / L.

[0060] In one embodiment, the electrolyte further comprises an additive, preferably fluoroethylene carbonate (FEC).

[0061] In one embodiment, the battery is a lithium-ion battery.

[0062] In a certain embodiment, the battery electrode sheet can be used as a positive electrode sheet or a negative electrode sheet of a battery depending on the composition of the battery.

[0063] The present invention also provides a use of the graphite-silicon composite material as described above in the preparation of battery pole pieces.

[0064] In one embodiment, the battery is a lithium-ion battery.

[0065] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0066] In the present invention, the room temperature is 20-30°C.

[0067] The graphite used in the examples was purchased from Shanghai Shanshan New Materials Co., Ltd.

[0068] In the examples, polyacrylonitrile was purchased from Sigma-Aldrich Co., Ltd.; specification: molecular weight Mw~15000, analytical grade.

[0069] Unless otherwise specified, the reagents and raw materials used in the present invention are commercially available.

[0070] The positive and progressive effects of the present invention are:

[0071] 1. The present invention finds that chemical bonding enables strong adhesion strength between nano-Si and graphite edge carbon nanotubes, thereby improving rate performance and cycle performance, wherein the rate performance is ≥90%, and the capacity retention rate after 500 cycles is ≥96%, thereby extending the life of the battery;

[0072] 2. The porous graphite matrix of the present invention can provide abundant channels for the rapid transmission of lithium ions, thereby improving the specific capacity of the battery, with a specific capacity of ≥640 mAh / g;

[0073] 3. The surface of silicon-graphite is coated with an outer coating layer to reduce the full-charge expansion rate, which is ≤20%. In particular, polyacrylonitrile (PAN) is used for coating. The resulting N atom doping not only improves the ion conductivity, but also increases the lithium storage active sites. The capacity retention rate is greatly improved after 500 weeks.

[0074] 4. The graphite-silicon composite material of the present invention has excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a SEM image of the graphite-silicon composite material obtained in Example 1; Note: the magnification is 500x, the electron beam acceleration voltage is 10kv, the length scale is 80μm, and the working distance is 7000mm;

[0076] Figure 2 This is the XRD pattern of the graphite-silicon composite material obtained in Example 1. DETAILED DESCRIPTION

[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0078] Example 1

[0079] (1) 2000 g of graphite was transferred to a rotary kiln. First, N2 was kept flowing through the furnace. The temperature was raised to 400°C at a rate of 1°C / min and maintained for 2 h. Then, the temperature was further raised to 800°C at a rate of 2°C / min. The gas in the furnace was converted from N2 to CO2 at a gas flow rate of 20 mL / min and maintained for 2 h. After natural cooling, the pore size of the porous graphite matrix was obtained to be 1.5-2 nm.

[0080] (2) 1000 g of the porous graphite matrix prepared above and 100 g of Ni(NO3)2·6H2O were added to a fusion machine at a rotation speed of 800 rpm for 5 min. The fused graphite-nickel nitrate mixture was then transferred to a reactor and calcined at 700°C for 0.5 h in a H2 atmosphere and then at 700°C for 2 h in a C2H2 atmosphere to form a porous graphite edge carbon nanotube structure (a porous graphite matrix with a distributed carbon nanotube structure).

[0081] (3) 500g of the material prepared in the above step (2) is placed in a fluidized bed, with 99.9999% high-purity silane (SiH4) as the silicon source, the flow rate of high-purity silane is 0.5 L / min, the flow rate of high-purity nitrogen is 1.25 L / min, the reaction temperature is 600°C, the reaction time is 70 min, and the pressure is 20KPa to obtain an intermediate product (a composite material coated with a nano-silicon layer); then the intermediate product is subjected to carbon coating in a gas phase rotary furnace, firstly nitrogen replacement is performed to evacuate the air in the furnace so that the oxygen content in the furnace body is less than 0.1ppm; then ethylene gas is introduced for gas phase coating, the coating temperature is 600°C, the gas flow rate of the carbon source is 0.5 L / min, the furnace tube speed is 50Hz, and the reaction time is 60 min to form an interface silicon carbide layer. The composite material (Go-Si product) coated with a carbon layer connected by silicon carbide is obtained by the above method.

[0082] (4) 500 g of the Go-Si product obtained in step (3) was added to a mixed solvent containing 500 mL of ethanol and 500 mL of water, and magnetically stirred for 2 h to obtain a Go-Si solution; 125 g of polyacrylonitrile (PAN) was added to 100 mL of N,N-dimethylformamide (DMF), and ultrasonicated for 10 min to completely dissolve it to obtain a PAN solution; then the Go-Si solution and the PAN solution were stirred on a magnetic stirrer for another 1 h to form a uniform solution. Then it was placed in an oven at 100 ° C for 8 h, and after drying, the material was added to a rotary kiln, heated to 650 ° C at a rate of 2 ° C / min in a N2 atmosphere, and kept warm for 4 h to prepare a graphite-silicon composite material.

[0083] The graphite-silicon composite material prepared is as follows Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the nano-silicon particles are uniformly deposited in the pore structure of the porous graphite matrix. Figure 2 It can be seen that in the prepared graphite-silicon composite material, the porous graphite matrix and the nano-silicon layer are connected by silicon carbide chemical bonds.

[0084] Example 2

[0085] (1) 2000 g of graphite was transferred to a rotary kiln. First, N2 was kept flowing through the furnace. The temperature was raised to 400°C at a rate of 1°C / min and maintained for 2 h. Then, the temperature was further raised to 800°C at a rate of 2°C / min. The gas in the furnace was converted from N2 to CO2 at a gas flow rate of 20 mL / min and maintained for 3 h. After natural cooling, the pore size of the porous graphite matrix was obtained to be 2.5-3.5 nm.

[0086] The remaining steps are the same as those in Example (1).

[0087] Example 3

[0088] Only step (2) was adjusted: 1000 g of the porous graphite matrix prepared above and 100 g of Ni(NO3)2·6H2O were added to a fusion machine at a rotation speed of 800 rpm and a fusion time of 5 min; then the fused graphite-nickel nitrate mixture was transferred to a reactor and calcined at 700°C for 0.3 h in a H2 atmosphere and then at 700°C for 2 h in a C2H2 atmosphere.

[0089] The remaining steps are the same as those in Example (1).

[0090] Example 4

[0091] Only step (4) was adjusted: 500 g of (3) was added to a mixed solvent containing 500 mL of ethanol and 500 mL of water, and magnetically stirred for 2 h; 200 g of polyacrylonitrile (PAN) was added to 100 mL of N,N-dimethylformamide (DMF), and ultrasonicated for 10 min to completely dissolve it; then the Go-Si solution and PAN solution were stirred on a magnetic stirrer for another 1 h to form a uniform solution. Then it was placed in an oven at 100 ° C for 8 h, and after drying, the material was added to a rotary kiln and heated to 650 ° C at a rate of 2 ° C / min in a N2 atmosphere, and kept warm for 4 h.

[0092] The remaining steps are the same as those in Example (1).

[0093] Comparative Example 1

[0094] Compared with Example 1, step (1) is omitted and step (2) is modified as follows: 1000 g of graphite and 100 g of Ni(NO3)2·6H2O are added to a fusion machine at a rotation speed of 800 rpm for a fusion time of 5 min; then the fused graphite-nickel nitrate mixture is transferred to a reactor and calcined at 700°C for 0.5 h in a H2 atmosphere and then calcined at 700°C for 2 h in a C2H2 atmosphere.

[0095] The remaining steps are the same as those in Example (1).

[0096] Comparative Example 2

[0097] Compared with Example 1, step (2) is missing, and the remaining steps are the same as those of Example (1).

[0098] Comparative Example 3

[0099] Compared with Example 1, step (4) is missing, and the remaining steps are the same as those of Example (1).

[0100] Effect Example

[0101] In order to compare and verify the above-mentioned embodiments 1-4 and comparative examples 1-3, the following button-type half-cell performance tests were conducted:

[0102] Negative electrode sheet preparation method:

[0103] A binder (LA132), a conductive agent (SP) and a solvent (H2O) were added to the graphite-silicon composite materials of Examples 1-4 and Comparative Examples 1-3, respectively, and the mixture was stirred to prepare a slurry. The slurry was then coated on a copper foil, and the electrode was obtained after drying and rolling. The addition ratio was: graphite-silicon: SP: LA132 = 7: 2: 1.

[0104] Preparation of button cells:

[0105] The prepared electrode is the positive electrode of the half-cell, the metal lithium sheet is the negative electrode, the separator is a polypropylene (PP) film, and the electrolyte is a 1 mol / L LiPF6 solution (the solvent is EC / EMC=1:1, and the additive is 20wt% FEC);

[0106] The button half-cell was tested for performance under the following test conditions: charge and discharge rate: 0.1 C; voltage range: 0.005-2 V. In addition, the full charge expansion test was also conducted on the embodiment and the comparative example: (thickness of the pole piece when the button half-cell is fully charged to 100% SOC - thickness of the pole piece before the test) / thickness of the pole piece before the test * 100%; the test results are shown in Table 1.

[0107] According to the method in the national standard GB / T 24533-2019 "Graphite Negative Electrode Materials for Lithium-ion Batteries", the specific surface area of ​​each silicon-carbon composite material obtained in Examples 1-4 and Comparative Examples 1-3 was tested, and the conductivity of each silicon-carbon composite material was tested using a four-probe tester; the test results are shown in Table 1.

[0108] Table 1

[0109]

[0110] It can be seen from Table 1 that the graphite-silicon composite materials prepared in Examples 1-4 have good first effect, specific capacity, fast charging performance and cycle performance, with first effect ≥92%, specific capacity ≥640mAh / g, rate performance ≥90%, capacity retention rate ≥96% after 500 cycles, full charge expansion ≤20%, and excellent comprehensive performance. In Comparative Example 1, since porous graphite was not used for silane deposition, poor first effect, specific capacity, rate performance and cycle performance were shown, among which the specific capacity dropped to 426mAh / g and the cycle performance dropped to 65%. In Comparative Example 2, due to the weak interaction between silicon and carbon, graphite and silicon are very prone to interface separation. Although the specific capacity has been improved, the rate performance and cycle performance have dropped significantly. In Comparative Example 3, since PAN coating was not performed, the specific surface of the graphite-silicon composite material was too large, and serious side reactions occurred with the electrolyte, resulting in a serious decline in the first effect, rate performance and cycle performance of the material.

Claims

1. A graphite-silicon composite material, characterized in that: The graphite-silicon composite material comprises a porous graphite matrix with a distributed carbon nanotube structure, a nano-silicon layer, a carbon layer and an outer coating layer; The nano silicon layer, the carbon layer and the outer coating layer are coated on the porous graphite substrate with distributed carbon nanotube structure from inside to outside in sequence; The nano silicon layer and the carbon nano tube structure are connected via silicon carbide chemical bonds.

2. The graphite-silicon composite material according to claim 1, characterized in that It meets one or more of the following conditions: (1) The pore size of the porous graphite matrix with distributed carbon nanotube structure is 0.5-5 nm, preferably 1.5-2 nm or 2.5-3.5 nm; (2) The pore volume of the porous graphite matrix with distributed carbon nanotube structure is 0.0015~0.5 cm 3 / g, preferably 0.45cm 3 / g; (3) The micropore ratio of the porous graphite matrix with distributed carbon nanotube structure is 0.5-0.9, preferably 0.85; (4) The nano-silicon layer is deposited in the pores and on the surface of the porous graphite matrix having the distributed carbon nanotube structure; (5) The carbon layer is an ethylene carbon layer, an acetylene carbon layer or a methane carbon layer, for example, an ethylene carbon layer; (6) The outer coating layer is a polyacrylonitrile layer; (7) The graphite-silicon composite material is composed of a porous graphite matrix with a distributed carbon nanotube structure, a nano-silicon layer, a carbon layer and an outer coating layer from the inside to the outside.

3. A method for preparing a graphite-silicon composite material, comprising the following steps: S1: fusing a porous graphite matrix with a metal catalyst precursor to obtain a mixture of the porous graphite matrix and the metal catalyst precursor; in the presence of a carbon source, the mixture of the porous graphite matrix and the metal catalyst precursor is subjected to a vapor deposition method to obtain a porous graphite matrix with a distributed carbon nanotube structure; S2: The silicon source is coated on a porous graphite substrate with a distributed carbon nanotube structure by a vapor deposition method to obtain a composite material coated with a nano-silicon layer; The temperature of the vapor deposition method is ≤ 900°C; S3: coating the carbon source on the composite material coated with the nano-silicon layer by a vapor deposition method to obtain a composite material coated with a carbon layer; S4: coating the composite material coated with the carbon layer with a coating agent to obtain a graphite-silicon composite material.

4. The method for preparing the graphite-silicon composite material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In S1, the metal catalyst precursor is a reducing metal catalyst precursor, preferably nickel nitrate or a nickel nitrate hydrate, cobalt nitrate or a cobalt nitrate hydrate, or iron nitrate or a iron nitrate hydrate, such as Ni(NO3)2·6H2O; (2) In S1, the mass ratio of the porous graphite substrate to the metal catalyst precursor is (5-15):1, preferably 10:1; (3) In S1, the porous graphite substrate and the metal catalyst precursor mixture are subjected to hydrogen reduction treatment before vapor deposition; the temperature of the hydrogen reduction treatment is preferably 500-1000°C, preferably 700°C; (4) In S1, the time of the hydrogen reduction treatment is preferably 0.1 to 1 h, preferably 0.3 h or 0.5 h; (5) In S1, the carbon source is ethylene gas, acetylene gas or methane gas, such as acetylene gas; (6) In S1, the temperature in the vapor deposition method is 500-1000°C; (7) In S2, the temperature of the vapor deposition method is 400-800°C, preferably 580-620°C, for example 600°C; (8) In S2, the deposition pressure of the vapor deposition method is 10-50 KPa, preferably 20 KPa; (9) In S2, the deposition time of the vapor deposition method is 0.1 to 5 hours, preferably 1.16 hours; (10) In S2, the silicon source is introduced into the fluidized bed as silane gas, preferably silane with a purity of 99.9999%; (11) In S2, the silane gas is SiH4.

5. The method for preparing the graphite-silicon composite material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) In S3, the vapor deposition is carried out in an atmosphere with an oxygen content of ≤0.1 ppm; (2) In S3, the vapor deposition temperature is 400-900°C, preferably 500-700°C, for example 600°C; (3) In S3, the carbon source is ethylene gas, acetylene gas or methane gas, such as ethylene gas; (4) In S3, the gas flow rate of the carbon source is 0.1-3 L / min, preferably 0.5 L / min; (5) In S3, the reaction time is 0.5 to 5 h, preferably 1 h; (6) In S4, the coating agent is polyacrylonitrile; (7) In S4, the mass ratio of the composite material coated with the carbon layer to the coating agent is 1:(0.1-1), preferably 1:(0.2-0.4), for example 1:025; (8) In S4, the coating further comprises the following steps: The mixture of the composite material coated with the carbon layer and the solvent and the mixture of the coating agent and the solvent are mixed, dried and heated to obtain a graphite-silicon composite material; Preferably, In S4, the coating solution is preferably stirred before coating, and the stirring time is 1 to 5 hours, for example, 2 hours; In S4, the coating is preferably dried after coating, the drying temperature is 80-120°C, preferably 100°C; the drying time is 5-10h, preferably 8h; In S4, the heating temperature is 550-700°C, for example, 650°C; In S4, the heating time is 4 to 6 hours, for example 4.5 hours.

6. The method for preparing the graphite-silicon composite material according to claim 4 or 5, characterized in that: It meets one or more of the following conditions: (1) In S1, the temperature of the hydrogen reduction treatment is 700°C; (2) Before S3, silicon is deactivated by passing an inert gas.

7. A graphite-silicon composite material obtained by the preparation method according to any one of claims 3 to 6.

8. A battery pole piece, characterized in that: It comprises the graphite-silicon composite material according to any one of claims 1, 2 and 7, a binder and a conductive agent; Preferably, The conductive agent is acetylene black; The binder is polyacrylic acid.

9. A battery, characterized in that: It comprises the battery pole piece, the separator and the electrolyte as claimed in claim 8; Preferably, it satisfies one or more of the following conditions: (1) The electrolyte is a LiPF6 solution, wherein the concentration of the solution is 1 mol / L; (2) The electrolyte further comprises an additive, preferably fluoroethylene carbonate; (3) The battery described is a lithium-ion battery.

10. Use of the graphite-silicon composite material according to any one of claims 1, 2 and 7 in a battery, wherein: The battery is a lithium ion battery.

Citation Information

Patent Citations

  • Negative electrode material of lithium ion battery, preparation method thereof and lithium ion battery

    CN112635733A